Dynamic Aspects of Macrophage Polarization during Atherosclerosis Progression and Regression - Peled, Michael; Fisher, Edward A. (Frontiers in Immunology, 2014)
It is well recognized that macrophages in many contexts in vitro and in vivo display a spectrum of inflammatory features and functional properties. A convenient system to group together different subsets of macrophages has been the M1(inflammatory)/M2(anti-inflammatory) classification. In addition to other sites of inflammation, it is now established that atherosclerotic plaques contain both M1 and M2 macrophages. We review results made possible by a number of recent mouse models of atherosclerotic regression that, taken with other literature, have shown the M1/M2 balance in plaques to be dynamic, with M1 predominating in disease progression and M2 in regression. The regulation of the macrophage phenotype in plaques and the functional consequences of the M1 and M2 states in atherosclerosis will also be discussed.